Venous thromboembolism risk and postpartum lying-in: Acculturation of Indian and Chinese women. (March 2018) - Melov, Sarah J.; Hitos, Kerry
Abstract: Objective: many cultures have a set time of traditional rest in the postpartum period. There is limited information on how this activity may potentially increase the risk of venous thromboembolism (VTE). We aimed to investigate VTE risk by determining the prevalence of the cultural practice of postpartum "lying-in", quantifying activity and determining the factors that influence this tradition in women from China and the Indian subcontinent (India, Bangladesh, Pakistan and Sri Lanka) at an Australian tertiary referral hospital. Design: we surveyed a prospective cohort of 150 women aged ≥ 18 years who self-identified culturally as from the Indian subcontinent or Chinese, at baseline (≥ 32 weeks gestation) and at follow-up (six to eight weeks postpartum). Demographic details collected included VTE risk factors such as caesarean section, lack of graduated compression stockings (GCS), postpartum haemorrhage greater than 1000 mL, comorbidities and immobility. We quantified postpartum activities and investigated factors that might influence inactivity. Results: there were 100 women identifying as from the Indian subcontinent and 50 women identifying as Chinese recruited at the baseline of over 32 weeks' gestation. Most of the study participants (85%) rested in the postpartum period for cultural reasons. Of the women surveyed, 51% rested in bed as much as possible in the postpartum period. We found a significant correlation between increased number of children and decreased overall immobility or rest ( P = 0.03). Overall, 91% of participants had relative live-in help, and this significantly increased the risk of immobility by more than six-fold (odds ratio [OR], 6.17; 95% CI, 1.6–23.5; P = 0.008). Furthermore, a vaginal compared to a caesarean birth increased immobility risk by almost 3.5 times (OR, 3.4; 95% CI, 1.20–9.4; P = 0.021). Conclusions: acculturation is highly individualised, however postpartum rest remains prevalent in women who identify themselves culturally as from the Indian subcontinent or as Chinese. Inactivity and comorbidities compounded the impact of cultural postpartum rest, and put women at increased risk for VTE. Implications for practice: targeted, culturally appropriate, postnatal education should include VTE-prevention information to women who intend to practise postpartum rest. Highlights: Worldwide VTE is a leading cause of maternal deaths in high resourced countries. 85% of postpartum women practiced 'lying-in' due to cultural beliefs. Postpartum relative live-in support was planned by 89% of women. 51% of women stated they rested in bed as much as possible postpartum. Culturally appropriate education can be based on evidence from this paper.